2022
DOI: 10.1017/s0959270922000314
|View full text |Cite
|
Sign up to set email alerts
|

The effects of powerlines on bustards: how best to mitigate, how best to monitor?

Abstract: Summary Bustards comprise a highly threatened family of birds and, being relatively fast, heavy fliers with very limited frontal visual fields, are particularly susceptible to mortality at powerlines. These infrastructures can also displace them from immediately adjacent habitat and act as barriers, fragmenting their ranges. With geographically ever wider energy transmission and distribution grids, the powerline threat to bustards is constantly growing. Reviewing the published and unpublished literature up … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 81 publications
(172 reference statements)
0
6
0
Order By: Relevance
“…Apparently, the experts' allegations provided with information and arguments to the Administration to reject (at least momentarily) several PPs and force the companies to modify the initial projects by relocating to olive groves, thus reducing their environmental impact. Such modifications also evidenced that the land use efficiency of the PPs is higher in olive groves than in the areas initially chosen (see below) and that the length of the evacuation lines, which are known to have a negative impact on many bird species [43,44], is reduced. Yet, current changes in environmental regulations (Royal Decree 11/2022 and amendments of Directive (EU) 2018/2001 with COM(2021)557 final) aim to exclude renewable energies from the environmental impact and public information procedure, replacing it with a process of granting express authorizations, based on environmental zoning designed by the Administrations.…”
Section: Discussionmentioning
confidence: 96%
“…Apparently, the experts' allegations provided with information and arguments to the Administration to reject (at least momentarily) several PPs and force the companies to modify the initial projects by relocating to olive groves, thus reducing their environmental impact. Such modifications also evidenced that the land use efficiency of the PPs is higher in olive groves than in the areas initially chosen (see below) and that the length of the evacuation lines, which are known to have a negative impact on many bird species [43,44], is reduced. Yet, current changes in environmental regulations (Royal Decree 11/2022 and amendments of Directive (EU) 2018/2001 with COM(2021)557 final) aim to exclude renewable energies from the environmental impact and public information procedure, replacing it with a process of granting express authorizations, based on environmental zoning designed by the Administrations.…”
Section: Discussionmentioning
confidence: 96%
“…A large-scale experiment demonstrated that line marking reduces power line collision mortality in large terrestrial birds, but not in bustards (Shaw et al, 2021). For these reasons, underground cabling is the only solution that completely prevents bird collisions (Silva et al, 2022). For instance, in Austria and Hungary, extensive underground cabling of distribution lines was implemented in an important area for great bustards.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, overhead power lines cause collision fatalities and are a major source of direct anthropogenic bird mortality (Loss et al, 2015), especially in large birds such as cranes, storks, or bustards (Bernardino et al, 2018). Bustards (family Otididae) are among the birds most vulnerable to collision with power lines, and collision losses represent the major cause of mortality in many of threatened species of this family (Burnside et al, 2015;Collar et al, 2017;Dutta et al, 2011;Garcia del Rey and Rodriguez-Lorenzo, 2011;Jenkins et al, 2011;Mahood et al, 2018;Marcelino et al, 2018;Marques et al, 2021;Reiter, 2000;Shaw, 2013;Shaw et al, 2018;Silva et al, 2010Silva et al, , 2022Uddin et al, 2021). The development of these infrastructures represents a global threat to bustards, which are among the world's most endangered birds (IUCN, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Over the past years, a total of 65 ha of suitable habitat have already been lost to solar power plant, and 148 ha of suitable habitat will be further lost if proposed plants are developed. The development of solar energy plants typically carries the extension of the power lines, which have been found to be a main threat to bustard species worldwide (Silva et al 2023). Moreover, Abbasanta has been strongly afflicted by a locust plague over the past four years.…”
Section: Current and Emerging Threatsmentioning
confidence: 99%